Recent amendments to Queensland legislation make mental health presentations to hospital emergency departments more difficult to scrutinise. (12th October 2021) - Clough, Alan R; Evans, Angela; Grant, Kristy; Graham, Veronica; Catterall, Janet; Lakeman, Richard; Gilroy, John; Pratt, Gregory; Petrucci, Joe; Stone, Richard
Abstract: The Queensland Police Service (QPS) and Queensland Ambulance Service may detain and transport persons experiencing major disturbances in their mental capacity to an ED for urgent care. Queensland's new mental health legislation (March 2017) makes this legal intervention difficult to scrutinise. For a large non‐metropolitan region, QPS records for emergency examination orders (EEOs) and emergency examination authorities (EEAs) were compared with annual reports of Queensland's Director of Mental Health and Chief Psychiatrist. From 2009–2010 to March 2017, QPS‐registered EEOs totalled 12 903 while annual reports attributed 9441 to QPS (27% fewer). From March 2017 to 2019–2020, QPS‐registered EEAs totalled 6887. Annual reports declared 1803 EEAs in total for this period, without distinguishing those registered by QPS from the Queensland Ambulance Service. Past year proportions of EEOs, however, indicate perhaps ~1100 originated with QPS (84% fewer). Information crucial for considered emergency mental healthcare responses for thousands of people is no longer readily available.